Contribution of the Nicaraguan Red de Protección social in reducing poverty / Wendy Joseph Cooper - Joseph Cooper, Wendy; Wendy Joseph Cooper (Oslo: University College, 2010)
According to the World Bank (2001) Nicaragua is one of the poorest countries in Latin America. In 1990s around half of the population was classified as poor, and about 17 percent as extremely poor. In rural areas the incidence of poverty was even greater with about 70 percent of the population living in extreme poverty (World Bank, 2001). Moreover, most of the poor Nicaraguans are involved in agricultural activities such as coffee production, since it is one of the main sources of export earning, employment and therefore income in rural areas (John Maluccio, 2005). In 2001, the coffee crisis experienced in Central America had a great effect on the economy of Nicaragua, 'The loss of profits in coffee production has increased unemployment, affecting all producers and workers in the supply chain, and where alternate employment was not secured it affected the affordability of health care, education, food, clothing, housing and other key indicators of quality of life in rural areas' (www.worldbank.org). The decline in the prices of coffee and the economy of many poor households calls for improvement of social safety net programs, of which RPS is an example. (John Maluccio, 2005). Red de Protección Social had a short history in Nicaragua. It was implemented from 2000-2006, to be used as a compensatory mechanism for the poor, who were badly affected by the coffee crisis and structural adjustment policies implemented in the country. There has been a lot of research examining the effect of the first stage of the program in reducing poverty and boosting human capital. Most of the research shows that indeed the program had a number of positive effects during its first phase. Less, however, is known about the second phase or the general effect of the program that also may contribute to the understanding of the important role the program played in reducing poverty. In this paper I reviewed the overall impact of the Nicaraguan RPS in reducing poverty. More specifically, I present and discuss the results of the program on a wide range of poverty indicators such as: education, household expenditures, labor participation, health and nutrition. The research approach used for this evaluation is based on qualitative methods. The examination was carried out through a secondary analysis of evaluation done by other scholars.
Index, Boards, maps, References, graphics
Keywords: 1. THESS-MASTER 2. SOCIAL PROTECTION 3. REDUCING POVERTY